Stopping gender based violence and harassment at work : the campaign for an ILO convention - Pillinger, Jane; Runge, Robin; King, Chidi (Women's work., 2022)
An analysis of the International Labour Organization's ground-breaking global Treaty on eliminating violence and harassment in the world of work and the ten-year campaign that led to its enactment from three authors who each played a key role in the campaign and the negotiation of the Convention.